EFEKTIFITAS INQUIRY TERBIMBING DAN INQUIRY BEBAS TERMODIFIKASI MELALUI EKSPERIMEN TERHADAP HASIL BELAJAR FISIKA DITINJAU DARI KEMAMPUAN AWAL, KREATIFITAS, KEMAMPUAN BERPIKIR ABSTRAK SISWA KELAS X SMA NEGERI 6 KOTA MADIUN TAHUN AJARAN 2010/2011 - Purwandari, Purwandari; Huriawati, Farida; Yusro, Andista Candra (Jurnal Pendidikan, 2012)
The objectives of this reseach are: (1) to help students choose the most suitable learning method, (2) to serve qualified learning to pass the threshold level, (3) to make up the average students mark in physics. The method of the study is experiment applied on students of Grade X, SMA 6 Madiun. The sample is taken under cluster-random sampling technique having class XC and XD. Data on students achievement are taken by cognitive test, those of prior achievement are taken by documentation technique, those of creativity and abstraction skill are taken by test. Hypothetical examination is done under factorial anava 2x2x2x2.The results show that: (1) there is a different influence between guided inquiry and free-modified inquiry technique (0.005 < 0.05), (2) there is influence of high and low prior achievement (0.000 < 0.05), (3) there is influence of high and low students creativity (0.039 < 0.05), (4) there is influence of high and low abstarction skill (0.014 < 0.05), (5) there is no interaction between guided and free-modified unquiry technique with students prior achievement (0.043 < 0.05), (6) there is interaction between guided and free-modified unquiry technique with students creativity (0.043 < 0.05), (7) there is interaction between guided and free-modified unquiry technique with students abstraction skill (0.032 < 0.05), (8) there is no interaction between guided and free-modified unquiry technique with students prior achievement, creativity and abstraction skill towards the achievement (0.595 > 0.05).Key words: guided inquiry technique, free-modified inquiry technique, experiment, achievement, prior achievement, creativity, abstraction skill